Progress in 3D Silicon Radiation Detectors - Dalla Betta, Gian-Franco; Povoli, Marco (Frontiers in Physics, 2022)
In the past few years, there has been an increasing interest toward 3D silicon radiation detectors. Owing to their unique architecture, 3D detectors provide a remarkable radiation hardness at relatively low bias voltage (hence low power dissipation), that makes them the most appealing solution for use in the innermost layers of tracking detectors in High Energy Physics (HEP) experiments. Besides this primary application, the use of 3D sensor technology has been extended also to other fields, like thermal neutron detection and microdosimetry for proton and ion therapy. In this paper, we will review the state of the art and on going efforts in 3D detectors, covering the main design and technological issues, as well as selected results from the experimental characterization and TCAD simulation.